Application of the Concept of Community Based Natural Resource Management in the Exploitation of Small Islands Forest Resources in Maluku Province - Holle, Eric Stenly (Budapest International Research and Critics University, 2021)
Law No. 27 of 2007 on The Management of Coastal Areas and Small Islands as a constitutional basis specifically regulates the management of small islands for various activities. But on the other side, the law does not specifically regulate the management of forest resources while exploitation activities carried out by forest utilization permit holders are more carried out on small islands in Maluku Province that have their own characteristics and vulnerabilities that cause various ecological, socio-cultural and economic problems. This article is a normative legal study that examines positive legal provisions, legal principles and legal doctrines using legal approaches and conceptual approaches related to the issues studied. The results showed that the basic principles of forest resource management based on the state through various policies and legislation proved to have caused various crises in the field of forestry that ultimately threaten the environment and the existence of indigenous legal communities on small islands. On that basis, it is necessary to change the concept of forestry development that focuses more on the forest resource management system based on the community or Communnity Based Natural Resource Management which aims to alleviate poverty, natural resource conservation and good governance that involves the community actively in every government policy in forest management.